Mapping of Stranded Marine Biota Incidents in 2025 in the Denpasar BPSPL Work Area: A Spatial Perspective - Febrianti, Nova; Indriyawan, Muji Wasis; Saputra, Dewa Gde Tri Bodhi; Jefri, Edwin (Jurnal Biologi Tropis, 2025)
Indonesia’s coastal areas experience frequent marine biota stranding events, particularly in regions with high human activity. This study aims to describe the spatial distribution of marine biota strandings recorded in 2025 within the working area of BPSPL Denpasar, covering Bali, East Java, West Nusa Tenggara, and East Nusa Tenggara Provinces. Data were collected from field response activities and reports submitted by local communities and related institutions, then analyzed descriptively and mapped using Geographic Information Systems (GIS) with ArcMap 10.8. A total of 21 stranding events were recorded, dominated by whales and sea turtles, with most individuals found dead (71.4%), resulting in burial as the most commonly applied handling method. Spatial analysis indicates that stranding events were mainly concentrated along the western–northern coast of Bali, the southern coast of East Java, and the northern coast of Timor Island. These findings demonstrate that GIS-based mapping is effective for identifying stranding-prone areas and can support improved response strategies and sustainable marine conservation efforts.